2006
DOI: 10.1021/jp054996h
|View full text |Cite
|
Sign up to set email alerts
|

Structural Study on Polymorphism of Cis-Unsaturated Triacylglycerol:  Triolein

Abstract: To clarify the influence of cis-unsaturation on solid-state structures of triacylglycerols (TAGs), the crystal structures of three crystalline phases (alpha, beta' and beta) of triolein [C3H5(OCOC17H33)3] were investigated by powder X-ray diffractometry and IR and Raman spectroscopy. The influence on the structural change of the alpha phase in the course of cooling was also studied. With respect to the subcell structure and conformational order of hydrocarbon chains in the beta and beta' phases, triolein resem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
45
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 30 publications
10
45
0
Order By: Relevance
“…3b). The WAXS pattern of the b'-phase shows exactly the same features as those reported previously [6,7]. It has to be noted that, apart from the two peak maximums assigned to O ' usually associated with b'-phases (Fig.…”
Section: Ooosupporting
confidence: 83%
See 2 more Smart Citations
“…3b). The WAXS pattern of the b'-phase shows exactly the same features as those reported previously [6,7]. It has to be noted that, apart from the two peak maximums assigned to O ' usually associated with b'-phases (Fig.…”
Section: Ooosupporting
confidence: 83%
“…This is the result of the packing density of the oleoyl hydrocarbon chains being direction dependent [6]. The WAXS pattern could be refined to suggest an orthorhombic unit cell (a so-called pseudo-hexagonal subcell) with two broad peaks corresponding to the 110 (d = 4.32 Å) and 200 (d = 4.01 Å) planes [6]. After isothermal crystallization at 223 K, increasing the temperature initiates the transformation of the a 1 -phase into the b'-phase (Fig.…”
Section: Ooomentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that temperature history has an influence on fat crystalline structures. Akita et al reported that triacylglycerol, for example, had approximately three crystal polymorphs 26 , and these crystal polymorphs were transformed rapidly by thermal treatment around the phase transition temperature owing to melt-mediated crystallization 27 . In this study, sample B was prepared by using a process that included thermal treatment near the phase transition temperature, suggesting transformation of crystalline structures for sample B.…”
Section: Resultsmentioning
confidence: 99%
“…, whereas C Ϫ O stretching from the ester moiety is observed around 1188-1178 cm ), which is characteristic of O ┴ chain packing (25)(26)(27). Even though the splitting of these bands is not clearly seen for didecanoylethanolamine, di- …”
Section: Synthesis and Characterization Of Daesmentioning
confidence: 96%